Public administration in the COVID-19 era: the deconstruction of common sense of the Malaysian public - Zamri, Zahid (Universiti Malaya Press, 2024)
The Malaysian government launched numerous public healthcare initiatives such as monitoring the Standard Operation Procedures (SOP), vaccination programmes, and other related efforts to curb the COVID-19 pandemic. However, the government received different responses from citizens towards such efforts. This chapter discusses the public's diverse opinions regarding their confidence and trust in the government's management of the crisis, which, in turn, deconstructed the existing common sense. Data were collected from observation of social media posts, online newspapers, and related videos to deconstruct the public's mindset when the crisis hit the country.